Matematyka
bambuś
2017-06-21 14:39:25
2 34 + 5 23= 7 12 • 2/5 = 4 1/3 : 4 = 6-5 2/3= 7 2/3 : 1 3/4= (6 2/5-1 3/8) : 2 1/2= 4-2,507= 4,1•2,3= 6,753•10-12,8= 6,32+48,3:10=
Odpowiedź
rutka
2017-06-21 17:15:46

a) 2 3/4 + 5 2/3 = 2 9/12 + 5 8/12 = 7 15/12 = 8 3/12 = 8 1/4 b) 7 1/2 x 2/5 = 15/2 x 2/5 = 3 (poskracaj ułamki) c) 4 1/3 : 4 = 13/3 x 1/4 = 13/12 = 1 1/12 d) 6 - 5 2/3 = 1/3 e) 7 2/3 : 1 3/4 = 23/3 : 7/4 = 23/3 x 4/7 = 92/21 = 4 8/21 f) (6 2/5 - 1 3/8) : 2 1/2 = (32/5 - 11/8) : 2 1/2 = (256/40 - 55/40) x 2/5 = 199/40 x 2/5 = 199/40 x 16/40 = 3184/1600 = 1 1584/1600 = 1 99/100 g) 4 - 2,507 = 1,493 h) 4,1 x 2,3 = 9,43 i) 6,753 x 10 - 12,8 = 67,53 - 12,8 = 54,73 j) 6,32 + 48,3 : 10 = 6,32 + 4,83 = 11,15

Dodaj swoją odpowiedź